The Paradigm of Critical Realism and Involving Educators in Policy Debates - Parra, Juan David (GIST – Education and Learning Research Journal, 2015)
Education policy debates in Colombia often exclude the voice of professional educators. The aim of this paper is to introduce Critical Realism as an alternative to dominant social research paradigms that enables the possibility of more inclusive education policies. The ontic and epistemic elements of CR make a call for an inter-paradigmatic dialogue to retrieve causal explanations by providing scientific value to first-hand living experiences of social actors. In the end, different researchers (i.e. statisticians and school teachers) have a crucial, but differentiated, role, in the quest for scientific discovery.